Late Holocene Heavy Metals Record of Jakarta Bay Sediments - Rina Zuraida; Riza Rahardiawan; Yani Permanawati; Indra Adhirana; Andrian Ibrahim; Nazar Nurdin; Haryadi Permana (BULLETIN OF THE MARINE GEOLOGY, 2018)
This paper reports copper, zinc, lead, cadmium, and chromium records of Jakarta Bay sediment since 600 AD and reonstruct environmental changes since that time. Jakarta Bay This study uses samples from a 150 cm long gravity core (TJ-17, 106.902488°E, 5.99381°S) that was acquired from the eastern part of Jakarta Bay in 2010 onboard RV Geomarin I by the Marine Geological Institute. Heavy metal content in Jakarta Bay sediments is used to track environmental changes onland from this site. Heavy metal concentration was analyzed using atomic absorption spectrometry on bulk samples that were taken in 5 cm interval. The results yield background level of Cu at 16 ppm, Zn at 75 ppm, Pb at 20 ppm, Cd at 0.01 – 0.15 ppm, and at Cr 80 ppm. Vertical record of heavy metals show two stages of environmental changes in the region: from 600 AD to 1600 AD and 1800 AD onward. These changes are interpeted as related to land use changes caused by human activity in the West Java region.